The impact of sentinel lymph node sampling versus traditional lymphadenectomy on the survival of patients with stage IIIC endometrial cancer. Issue 6 (14th April 2021) - Nasioudis, Dimitrios; Byrne, Maureen; Ko, Emily M; Giuntoli II, Robert L; Haggerty, Ashley F; Cory, Lori; Kim, Sarah H; Morgan, Mark A; Latif, Nawar A
Abstract : Objective: To investigate the survival of patients with lymph node positive endometrial carcinoma by type of surgical lymph node assessment. Methods: Patients diagnosed between January 2012 and December 2015 with endometrial carcinoma and uterine confined disease and nodal metastases on final pathology who underwent minimally invasive hysterectomy were identified in the National Cancer Database. Patients who had sentinel lymph node biopsy alone or underwent systematic lymphadenectomy were selected. Overall survival was evaluated following generation of Kaplan–Meier curves and compared with the log rank test. A Cox model was constructed to evaluate survival after controlling for confounders. Results: A total of 1432 patients were identified: 1323 (92.4%) and 109 (7.6%) underwent systematic lymphadenectomy and sentinel lymph node biopsy only, respectively. The rate of adjuvant treatment was comparable between patients who had sentinel lymph node biopsy alone and systematic lymphadenectomy (83.5% vs 86.6%, p=0.39). However, patients who had sentinel lymph node biopsy were less likely to receive chemotherapy alone (13.6% vs 36.6%, p<0.001) and more likely to receive radiation therapy alone (19.8% vs 5.4%, p<0.001) compared with patients who had systematic lymphadenectomy. There was no difference in overall survival between patients who had sentinel lymph node biopsy alone and systematic lymphadenectomy (p=0.27 from log rank test), and 3 year overall survival rates were 82.2% and 79.4%, respectively (p>0.05). After controlling for confounders, there was no difference in survival between the systematic lymphadenectomy and sentinel lymph node biopsy alone groups (hazard ratio 0.82, 95% confidence interval 0.46 to 1.45). Conclusions: Performance of sentinel lymph node biopsy alone was not associated with an adverse impact on survival in patients with lymph node positive endometrial cancer.